Interaction analysis between BLK rs13277113 polymorphism and BANK1 rs3733197 polymorphism, MMEL1/TNFRSF14 rs3890745 polymorphism in determining susceptibility to rheumatoid arthritis - Hua Huang; Si-Chao Huang; Dong-Jin Hua; Qing-Qing Sun; Han Cen; Xia-Fei Xin (Taylor & Francis Group, 2017)
Two pairwise genetic interactions (B cell lymphocyte kinase (BLK) rs13277113,B cell scaffold protein with ankyrin repeats 1 (BANK1) rs3733197and BLK rs13277113 membrane metalloendopeptidase like 1 (MMEL1)/ tumor necrosis factor receptor superfamily member 14 (TNFRSF14) rs3890745) have been demonstrated in determining susceptibility to rheumatoid arthritis (RA) without replication, thus this study was performed to examine whether abovementioned genetic polymorphisms were associated with RA and further tests were performed to see whether aforementioned genetic interactions existed in RA among Chinese population. A total of 328 patients with RA and 449 healthy control subjects were included in the current study. The polymorphisms were genotyped using the ligase detection reaction-polymerase chain reaction (LDR-PCR) technology. The association of RA with each polymorphism was analyzed by multivariate logistic regression model. Interaction analysis was done by multiple methods. Significant difference in genotype distribution of BLK rs13277113 polymorphism between RA patients and healthy controls was found (p = 1.01 × 10−2). The major allele A of BLK rs13277113 polymorphism was significantly increased in RA patients compared with controls (OR = 1.36, 95% CI = 1.08-1.71, p = 9.27 × 10−3). Significant association of RA with the major allele A of BLK rs13277113 polymorphism under dominant model was also detected (OR = 2.74, 95% CI = 1.42-5.29, p = 2.73 × 10−3). However, we did not find significant association between neither BANK1 rs3733197 polymorphism nor MMEL1/TNFRSF14 rs3890745 polymorphism and RA. Non-significant evidence was found for neither additive nor multiplicative interaction for these two pairwise genetic polymorphisms (BLK rs13277113-BANK1 rs3733197; BLK rs13277113-MMEL1/TNFRSF14 rs3890745). Significant association of RA with G allele of BANK1 rs3733197 polymorphism was only found among individuals carrying A/A genotype of the BLK rs13277113 polymorphism (OR = 1.49, 95% CI = 1.01-2.18, p = .04). In summary, our results indicated that the BLK rs13277113 polymorphism was involved in the genetic background of RA in Chinese population and the association of BANK1 rs3733197 polymorphism with RA was dependent on the genotype of BLK rs13277113 polymorphism, highlighting B-cell response implicated in the pathogenesis of RA.